Hepatoprotective Activity of Roots of Desmodium gangeticum (Linn.) DC - Prasad, M.V.V.; Balakrishna, K.; William Carey, M. (Asian Journal of Chemistry, 2016)
The chloroform extract of roots of Desmodium gangeticum (Linn.) DC was tested for hepatoprotective activity against carbon tetrachloride induced liver damage in rats. The evaluation was done by measuring the increased serum levels of total proteins and decreased levels of bilirubin (total and direct), serum glutamate oxaloacetate transaminase and serum glutamate pyruvate transaminase in the group of rats pretreated with the chloroform extract.